Computer modeling of operation of existing wastewater treatment plant during its reconstruction - Protsenko, Serhii; Kizyeyev, Mykola; Novytska, Olha (Видавництво Львівської політехніки, 2023)
The effectiveness of the computer modeling use of wastewater treatment processes during the implementation of planned measures was proved on the example of reconstruction of wastewater treatment plant (WWTP) of one of the large cities of Ukraine. Modeling of technological processes of wastewater treatment was performed for six modes of operation of WWTP: according to the operating technological scheme; during the implementation of four stages of its reconstruction and after the completion of all works of the reconstruction of WWTP according to new technological scheme. It is shown that, according to the technological sequence of construction and installation works adopted in the design, WWTP at all stages of its reconstruction are able to provide the standard quality of treated wastewater according to the main pollution indicators (COD, BOD5, ammonium nitrogen, total suspended solids (TSS)). It is also shown that gradual reduction of pollution concentrations of nitrogen nitrates and phosphorus phosphates will be provided in the process of successively transferring the operation of the reconstructed WWTP according to new technological scheme and the normative requirements for their content in effluent will be achieved.
Keywords: reconstruction of WWTP; computer modeling; nitrite-denitrification; dephosphorization